Nudge, nudge, wink, wink: love, sex and gay men with intellectual disabilities – a helping hand or a human right?. (17th December 2012) - Abbott, D.
Abstract: Background: How do human rights help us with the experiences of people with intellectual disabilities (ID) who face discrimination and barriers in their sexual lives? Men with ID who are gay face a whole range of rights violations when it comes to exercising their sexual identity. How can such a seemingly marginalised group draw on rights based claims for better and equal treatment? This paper explores how the power of men's own stories may usefully challenge prevailing social norms and in turn strengthen human rights claims in this area. It also reflects on the challenges posed to such an agenda by current economic difficulties and changes in the organisation of adult social care in the UK. Method: The paper draws on empirical research with gay men with ID completed in the UK in 2005 and briefly revisits some key messages from the data. It also considers the wider literature on the power and possibilities of human rights, 'intimate stories' and translating human rights into everyday change. Conclusions: Gay men with ID tell powerful stories of love, longing and exclusion. Such stories have the capacity to transform wider social attitudes and in turn strengthen the rights claims of this marginalised groups. There are question marks about the possibility of such change in a time of austerity and the broader move in the UK's welfare state from the collective to the individual consumer of services. However, the telling of men's 'intimate stories' creates an almost unassailable challenge to current discriminatory practices and norms.